BAZI KISMİ DİFERENSİYEL DENKLEMLERİN BERNOULLİ ALT-DENKLEM FONKSİYON METODU İLE ÇÖZÜMLERİNİN İRDELENMESİ - EMİR, DİLARA GİZEM (Fırat Üniveristesi, 2016)
Bu tez dört bölümden oluşmaktadır. Birinci bölümde; daha sonraki bölümlerde kullanılacak olan temel tanım ve teoremler verildi. İkinci bölümde; Bernoulli Alt-Denklem Fonksiyon metodunun genel yapısı verildi. Üçüncü bölümde; Vakhnenko-Parkes ve PHI-four denklemlerinin Bernoulli alt-denklem metodu ile çözümleri yapıldı. Mathematica 9 programı kullanılarak çözümlerin iki ve üç boyutlu grafiği çizildi. Dördüncü bölümde ise, elde edilen analitik çözümler göz önüne alınarak kapsamlı bir sonuç verildi.

This study consists of the four chapters. In the first chapter, it has been given information on some fundamental definitions and theorems which have been used in following chapters. In chapter two, it has been given information on general structure of Bernoulli Sub-Equation Function. In chapter three, Vakhnenko-Parkes ve PHI-four equations have been solved with Bernoulli Sub-Equation Method. 2D and 3D graphics of the solutions have been drawn used Mathematica 9 program. In chapter four, it has been given a comprehensive conclusion by taking into account analytical solutions obtained in this study.
Analysis of solutions of some partial differential equation with the method of bernoulli sub-equation function
Keywords: Matematik